An Investigation Into the Relationship Between Taq1 and Apa1 Polymorphisms of the Vitamin D Receptor Gene and the Development of Osteoarthritis - Banu BAYRAM; Bülent Emrah SAYIN; Züleyha TÜRKOĞLU; Şeyma SOFUOĞLU; Fezan Mutlu ŞAHİN3 (Archives of Rheumatology, 2011)
Objectives: This study aims to determine whether Vitamin D receptor (VDR) gene TaqI and ApaI polymorphisms are involved in the development of osteoarthritis in the Turkish population. Patients and methods: In this study, genomic DNA was isolated from 140 subjects (95 patients with osteoarthritis and 45 healthy controls). The DNA was amplified with specific primers by polymerase chain reaction and the restriction fragment length polymorphism (RFLP) technique was used to analyze the VDR gene TaqI and ApaI polymorphism genotypes. Polymerase chain reaction-RFLP products were assessed with and ultraviolet transilluminator by being exposed to agarose gel electrophoresis. Results: In terms of the genotype distributions and the allele frequencies of VDR gene TaqI and ApaI polymorphisms, there was no statistically significant difference (p>0.05) between the osteoarthritis patients and the controls. In addition, there was also no statistically significant difference between the genotypes and clinical characteristics of the patients or controls. Conclusion: In conclusion, the results of the present study suggest that VDR gene TaqI and ApaI polymorphisms are not involved in the development of osteoarthritis in the studied Turkish population.